2022
DOI: 10.3390/app12042256
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effects of Fluoxetine on Danio rerio: A Biochemical and Behavioral Perspective

Abstract: Fluoxetine is an antidepressant widely used to treat depressive and anxiety states. Due to its mode of action in the central nervous system (selective serotonin reuptake inhibitor (SSRI)), it becomes toxic to non-target organisms, leading to changes that are harmful to their survival. In this work, the effects of fluoxetine on juvenile zebrafish (Danio rerio) were evaluated, assessing biochemical (phase II biotransformation—glutathione S-transferase (GST), neurotransmission—acetylcholinesterase (ChE), energy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…For example, Chen et al (2018a) showed that in Pseudorasbora parva juveniles, a shortterm exposure (4 h) to 50 and 200 μg/L, resulted in CAT activity increase at the lowest concentration, while a chronic exposure (42 days) caused an inhibition at the highest concentration. Correia et al (2022) showed a decrease in GPx activity in juvenile D. rerio exposed for 21 days to 10 μg/L fluoxetine. Effects on the levels of the non-protein thiol with important role on non-enzymatic antioxidant defense, GSH has also been reported in Pseudorasbora parva juveniles exposed for 4 h to 50 μg/L fluoxetine, displaying an increase in hepatic GSH (153 %), at 200 μg/L.…”
Section: Oxidative Stressmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, Chen et al (2018a) showed that in Pseudorasbora parva juveniles, a shortterm exposure (4 h) to 50 and 200 μg/L, resulted in CAT activity increase at the lowest concentration, while a chronic exposure (42 days) caused an inhibition at the highest concentration. Correia et al (2022) showed a decrease in GPx activity in juvenile D. rerio exposed for 21 days to 10 μg/L fluoxetine. Effects on the levels of the non-protein thiol with important role on non-enzymatic antioxidant defense, GSH has also been reported in Pseudorasbora parva juveniles exposed for 4 h to 50 μg/L fluoxetine, displaying an increase in hepatic GSH (153 %), at 200 μg/L.…”
Section: Oxidative Stressmentioning
confidence: 88%
“…Rapid light/dark changes have also been used for the assessment of stress responses. For example, Correia et al (2022) observed in D. rerio juveniles exposed to 1 and 10 μg/L Females followed less of their potential partners (all concentrations tested).…”
Section: Locomotor Behaviormentioning
confidence: 97%
“…Thoré et al (2020) reported that male Nothobranchius furzeri exposed to 5.3 µg/L of fluoxetine, another common SSRI, for 8 weeks displayed an increase in sociability by 34%, whereas Hong et al (2021) found that zebrafish exposed to high concentrations of sertraline, fluoxetine, and citalopram showed a decline in sociability after 21 days. In contrast, Correia et al (2022) concluded that fluoxetine did not alter the social behavior of zebrafish at a concentration ≥0.1 µg/L for 21 days.…”
Section: Discussionmentioning
confidence: 91%